2023
DOI: 10.3390/ijms241512302
|View full text |Cite
|
Sign up to set email alerts
|

EP300 as a Molecular Integrator of Fibrotic Transcriptional Programs

Karla Rubio,
Alejandro Molina-Herrera,
Andrea Pérez-González
et al.

Abstract: Fibrosis is a condition characterized by the excessive accumulation of extracellular matrix proteins in tissues, leading to organ dysfunction and failure. Recent studies have identified EP300, a histone acetyltransferase, as a crucial regulator of the epigenetic changes that contribute to fibrosis. In fact, EP300-mediated acetylation of histones alters global chromatin structure and gene expression, promoting the development and progression of fibrosis. Here, we review the role of EP300-mediated epigenetic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…HSP90AA1, a molecular chaperone involved in protein folding and stabilization, is potentially implicated in alcoholic hepatitis and cirrhosis ( Choudhury et al, 2020 ; Costa et al, 2020 ). EP300, a histone acetyltransferase, has been linked to multiorgan fibrosis through the TGFβ pathway, suggesting epigenetic regulation of fibrogenesis and progression ( Rubio et al, 2023 ). These findings provide avenues for future studies of the precise mechanisms by which CDK4/6 inhibitors influence these key molecular players in liver pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90AA1, a molecular chaperone involved in protein folding and stabilization, is potentially implicated in alcoholic hepatitis and cirrhosis ( Choudhury et al, 2020 ; Costa et al, 2020 ). EP300, a histone acetyltransferase, has been linked to multiorgan fibrosis through the TGFβ pathway, suggesting epigenetic regulation of fibrogenesis and progression ( Rubio et al, 2023 ). These findings provide avenues for future studies of the precise mechanisms by which CDK4/6 inhibitors influence these key molecular players in liver pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HATs regulate gene silencing or transcription through the modulation of the acetylation of histones, thus orchestrating gene expression to induce liver fibrosis [ 110 , 111 ]. Additionally, histone acetylation has been implied in pulmonary and cardiac fibrosis [ 10 ], performed through the activity of p300 HAT [ 112 , 113 ]. An interesting discovery enriched the molecular scenario by demonstrating that p300 HAT induces the fibrotic process in IPF and cardiac fibrosis via EMT and EndMT, respectively [ 114 ].…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
“…Depending on the tissue, molecular characteristics, and grade of organ dysfunction, fibrosis is considered a life-threatening condition. Renal, cardiac, liver and pulmonary fibrosis are the major causes of death, but several studies have identified common altered epigenetic regulation that could be a potential approach to target multi-organ fibrosis ( Rubio et al, 2023b ). Particularly, pulmonary fibrosis (PF) is the irreversible phenotype of all interstitial lung diseases (ILDs), characterized by progressive thickening of lung tissue that reduces gas exchange and ultimately leads to progressive hypoxemia, respiratory failure, and mortality ( Zhu et al, 2023 ).…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%